Endogenous glucocorticoid signaling in chondrocytes attenuates joint inflammation and damage. Issue 1 (19th September 2017) - Tu, Jinwen; Stoner, Shihani; Fromm, Phillip D.; Wang, Tingyu; Chen, Di; Tuckermann, Jan; Cooper, Mark S.; Seibel, Markus J.; Zhou, Hong
Abstract : Previous studies demonstrated that endogenous glucocorticoid signaling in osteoblasts promotes inflammation in murine immune arthritis. The current study determined whether disruption of endogenous gluco‐corticoid signaling in chondrocytes also modulates the course and severity of arthritis. Tamoxifen‐inducible chondrocyte‐targeted glucocorticoid receptor‐knockout (chGRKO) mice were generated by breeding GR flox/flox mice with tamoxifen‐inducible collagen 2a1 Cre (Col2a1‐CreER T2 ) mice. Antigen‐induced arthritis (AIA) and K/BxN serum transfer‐induced arthritis (STIA) were induced in both chGRKO mice and their Cre‐negative GR flox/flox littermates [wild type (WT)]. Arthritis was assessed by measurement of joint swelling and histology of joints collected at d 14. Neutrophil activity and gene expression patterns associated with cartilage damage were also evaluated. In both arthritis models clinical (joint swelling) and histologic indices of inflammatory activity were significantly greater in chGRKO than in WT mice. The STIA model was characterized by early up‐regulation of CXCR2/CXCR2 ligand gene expression in ankle tissues, and significant and selective expansion of splenic CXCR2 + neutrophils in chGRKO arthritic compared to WT arthritic mice. At later stages, gene expression of enzymes involved in cartilage degradation was up‐regulated in chGRKO but not WT arthritic mice. Therefore, we summarize that chondrocytes actively mitigate local joint inflammation, cartilage degradation and systemic neutrophil activity via a glucocorticoid‐dependent pathway.—Tu, J., Stoner, S., Fromm, P. D., Wang, T., Chen, D., Tuckermann, J., Cooper, M. S., Seibel, M. J., Zhou, H. Endogenous glucocorticoid signaling in chondrocytes attenuates joint inflammation and damage. FASEB J. 32, 478‐487 (2018). www.fasebj.org